Testing the Antibacterial Activity of Red Ginger Essential Oil and Red Ginger Methanol Extract - Kapelle, Imanuel Berly Delvis; Mauhurry, Mirella Fonda; Neite, Prisca Nelcy (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
The red ginger plant is a spice plant used in traditional medicine and has the potential to be antibacterial. This research aims to isolate and identify red ginger essential oil, extract red ginger, and test antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria. Red ginger essential oil is obtained by steam distillation, while red ginger extract is obtained using the maceration method with methanol solvent. Red ginger essential oil yielded 0.13%, and red ginger extract was 12%. The phytochemical test results of red ginger essential oil contain tannin and sopinin, while red ginger extract contains flavonoids, tannin and saponin. The results of analysis using GCMS show that there are 31 components of red ginger essential oil, with the main compounds 2-butanone-4-(3-hydroxy-2-methoxyphenyl) (21.51%) and Zingerone (15.10%). The GCMS test results for red ginger methanol extract obtained 31 components, with the main components being citral (24.05%). The results of antibacterial testing of red ginger extract did not provide activity in inhibiting bacteria, whereas red ginger essential oil at a concentration of 100% provided inhibition of the growth of E. coli bacteria (14.00 Â± 2.00 mm) and at a concentration of 40% for S. aureus bacteria (22.67 Â± 2.31 mm).